PELAKSANAAN DISKRESI KEPOLISIAN DALAM PENYIDIKAN TINDAK PIDANA PERJUDIAN DAN ZINA TERKAIT DENGAN PENERAPAN QANUN DI WILAYAH HUKUM POLDA ACEH - Moh. Basori; Marlina Marlina; Mustamam Mustamam (LPPM YPITI, 2021)
The application of criminal law and qanun jinayat in the jurisdiction of the Aceh Regional Police, that in the act of Jarimah as regulated in the qanun, is also regulated in the KUHP or criminal provisions outside the KUHP, then what applies is the Jarimah rule in the Jinayat legal Qanun. The authority to investigate the finger as contained in the Qanun Jinayat lies with the National Police and Civil Servant Investigators. The reasons for police discretion in investigating criminal acts of gambling and adultery are related to the implementation of Qanun Jinayat, influenced by factors of legal substance, legal structure and legal culture of society. Overcoming the dualism of material and formal criminal law in enforcing the criminal act of gambling and adultery in the jurisdiction of the Aceh Regional Police, by adjusting the legal substance in Qanun Number 7 of 2013 concerning Jinayat Procedure Law with the provisions of the Criminal Procedure Code.